Employee Loyalty And Engagement Mediating The Impact Of Transformational Leadership On Employee Performance - Dharmawati, Ni Luh Eka; Subawa, Nyoman Sri (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study explores the factors affecting the quality of services at Puskesmas, specifically Puskesmas Kediri II. The quality of healthcare services plays a crucial role in enhancing community satisfaction and the success of national health programs. Based on the Regulation of the Minister of Health No. 30 of 2022, this research analyzes the current condition of service quality and the challenges faced in meeting those standards. The methodology used is a qualitative approach with in-depth interview techniques. The informants include the head of the Puskesmas, doctors, nurses, program coordinators, and patients. Data were analyzed using NVIVO Pro 12. The results indicate that the quality of services at Puskesmas Kediri II is categorized as good, although it faces challenges such as limited human resources and inadequate infrastructure. Recommended strategies include improving waiting area facilities, renovating to enhance patient privacy, and regularly maintaining toilets and sanitation facilities. This study recommends increasing the number of healthcare personnel and improving infrastructure to meet the standards set by Regulation of the Minister of Health No. 30 of 2022.